The Nordenskièold collection of Eskimo material culture from Port Clarence, Alaska / Fieldiana, Anthropology, new series, no.14 - VanStone, James W. (Chicago, Ill. : Field Museum of Natural History, 1990)
Collections of the Folkens Museum Etnografiska in Stockholm, Sweden, contain 246 ethnographic objects collected by A. E. Nordenskièold at Port Clarence, Alaska, during his circumnavigation of Europe and Asia in 1879-1880. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of western Alaskan Eskimo culture, especially those of Field Museum's Port Clarence and Kotzebue Sound collections (VanStone, 1976, 1980). Includes bibliographical references (p. 26-27). Collections of the Folkens Museum Etnografiska in Stockholm, Sweden, contain 246 ethnographic objects collected by A. E. Nordenskièold at Port Clarence, Alaska, during his circumnavigation of Europe and Asia in 1879-1880. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of western Alaskan Eskimo culture, especially those of Field Museum's Port Clarence and Kotzebue Sound collections (VanStone, 1976, 1980). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).